ANALISIS KETERLIBATAN TENAGA KERJA WANITA DALAM USAHA AGROINDUSTRI BUAH DI KABUPATEN MADIUN - Mustika Wardhani, Ratna; Rekyani Puspitawati, Indah (JURNAL AGRI-TEK, 2014)
Agro-industry in an effort to help employment, especially women, far less attention to or ignore the involvement of women, whereas the survival of rural agro-industry is based on the employment of women. So the existence of rural agro-industry in a very big role in helping improve the economy of rural families to see the involvement of women who donated for the survival of the agro-industry. The purpose of the study are as follows: a. To determine the area of women's participation as a labor of agro-industry research, b. To determine labor productivity generated in the agro-industry business, c. To determine the contribution given to the women workers of agro-industry businesses. The method used in determining the respondent is a census method, analysis of the data used in this research is the analysis of the description and analysis of the data used to determine participation, labor productivity and contribution of women in the agro-industry businesses. From the research that has been conducted on fruit agro-industry in the Village District of Kare Kuwiran Madiun County, obtained the following conclusions: (1) The participation of women workers in agro-industry fruit (banana and jackfruit chips) of 2.07%, this indicates that the participation of women to work very small. (2) The productivity of female workers in the agro-industry fruit (banana and jackfruit chips) amounted to 0,339 kg / h, this indicates that the productivity of women workers in the fruit agro-industry to generate products every hour is very low at just 0,339 kg. (3) Contributions of women workers in agro-industry fruit (banana and jackfruit chips) amounted to 64.6%, this indicates that the contribution of women in work in the fruit agro-industry is quite large compared to the contribution of male workers.Keywords: Agro-Industry, male wokers